Africa Agriculture Transformation Scorecard: performance and lessons. South Africa - Makabanyane, W.; Nhlengethwa, Sibusiso; Matchaya, Greenwell C.; Bongeka, M.; Heidi, P.; Greffiths, Ikhothatseng Jacob; Fakudze, Bhekiwe (Regional Strategic Analysis and Knowledge Support System for Southern Africa, 2021)
This brief highlights South Africa’s performance in the second BR and assesses challenges faced and lessons learned by the South Africa team during the review process. The brief also reviews policy and programmatic changes in South Africa that can be attributed to the first (2017) and second BRs. It concludes by highlighting required policy actions for South Africa to meet the Malabo commitments by 2025.